1997
DOI: 10.1007/pl00004933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of YM934, a KATP channel opener, on airway hyperresponsiveness induced by platelet activating factor in guinea-pigs

Abstract: The effect of YM934 (2-(3,4-dihydro-2,2-dimethyl-6-nitro-2H-1, 4-benzoxazin-4-yl)pyridine N-oxide) on airway hyperresponsiveness induced by platelet activating factor (PAF) was investigated in anesthetized guinea-pigs. Bronchoconstrictor responses to histamine were enhanced by intravenous (i.v.) infusion of PAF (600 ng/kg/h for 1 h). The KATP channel opener, YM934 (10-100 micrograms/ kg), given by i.v. bolus injection or i.v. infusion (75 min) dose-dependently inhibited this PAF-induced airway hyperresponsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The 12)] which is a potent vasodilator, that is 3-times more potent than LCRK, with particularly pronounced effect on coronary artery [92]. YM-934 (52) has been extensively evaluated in an attempt to delineate its pharmacological profile on cardiovascular [93][94][95], respiratory [96,97], and urinary [98,99] systems. A recent article by Astellas Pharmaceutical confirmed that a non-hypotensive dose of YM-934 significantly decreased coronary peripheral vascular resistances, increased coronary flow and enhanced myocardial recovery from transient coronary flow interruption in a dog model of impaired coronary circulation similar to unstable angina [100].…”
Section: Benzoxazinesmentioning
confidence: 99%
“…The 12)] which is a potent vasodilator, that is 3-times more potent than LCRK, with particularly pronounced effect on coronary artery [92]. YM-934 (52) has been extensively evaluated in an attempt to delineate its pharmacological profile on cardiovascular [93][94][95], respiratory [96,97], and urinary [98,99] systems. A recent article by Astellas Pharmaceutical confirmed that a non-hypotensive dose of YM-934 significantly decreased coronary peripheral vascular resistances, increased coronary flow and enhanced myocardial recovery from transient coronary flow interruption in a dog model of impaired coronary circulation similar to unstable angina [100].…”
Section: Benzoxazinesmentioning
confidence: 99%